The fall and rise of market power in Europe - John P. Weche Gelübcke; Achim Wambach (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
This paper presents an analysis of the recent developments of average market power in Europe by using a broad firm-level database for EU member states. To indicate competitive pressure at the firm-level, markups are estimated following De Loecker (2011), and De Loecker and Warzynski (2012). The analysis reveals a sharp drop in markups during the crisis, followed by a post-crisis increase. The European average has not yet reached its pre-crisis level, which is in contrast to results for the US, where average markups have climbed to pre-crisis levels already in 2011. There is significant heterogeneity among European economies and the pre-crisis levels do have been exceeded in some countries.
Keywords: E2; D2; D4; L1; 330; Market Power; Markups; Europe; Crisis